Federal Complexity and Perception of State Party Ideology in the United States. Issue 4 (24th May 2018) - Bishop, Bradford H
Abstract: Scholarship has established that ideological positions offered by state parties differ substantially from the national parties, and from one another. However, less attention has been devoted to investigating whether ordinary people are aware of the ideological distinctiveness of state parties. In particular, do people notice that their state party is ideologically different than the national party? In this article, I draw upon theories of low information rationality to develop an account of public reasoning about state parties. I analyze public opinion about state parties using an original survey fielded as part of the 2012 Cooperative Congressional Election Study. I find limited evidence that ordinary people are responsive to the actual legislative behavior of state parties. Instead, individuals' judgments about state party ideology may be rooted in inferences drawn from national-level politics. The findings support arguments that a complicated federal structure obscures the role of state-level actors in the policymaking process.